Strategies Used By Religious And Ethics Teachers To Improve The Attitudes Of 10th-Grade Social Studies Students Toward Teachers In The Digital Age (A Case Study At Ma Hasyim Asy’ari Bangsri) - Salma Mufarrikhatul Walidiyah; Alex Yusron Al-Mufti (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the challenges faced and the strategies implemented by Aqidah Akhlak teachers in strengthening students’ manners toward teachers in the digital era at MA Hasyim Asy’ari Bangsri. This research employs a qualitative approach with a case study design to gain an in-depth understanding of the phenomenon based on real conditions in the field. Data collection techniques include in-depth interviews, observations, and documentation, involving the principal, Aqidah Akhlak teachers, and tenth-grade social science students as informants. Data analysis was conducted interactively through the stages of data reduction, data display, and conclusion drawing, while the validity of the data was ensured through source and method triangulation. The findings indicate that the main challenges faced by teachers include diverse student characteristics, low awareness of manners and etiquette, and the negative influence of internet and social media usage. In addition, teachers’ limited ability to supervise students outside the school environment, lack of parental control, and the influence of peer environments also become significant obstacles in strengthening students’ manners. To address these challenges, teachers implement several strategies, including providing role models (uswah hasanah), continuously reinforcing and habituating moral values, filtering and guiding the use of social media, and integrating moral values into local content subjects through the study of Aqidatul Awwam and Ta’limul Muta’allim.